EVALUATION OF ANTIOXIDANT AND ANTIGLYCATION ACTIVITIES OF VARIOUS SOLVENT FRACTIONS OF CISSUS QUADRANGULARIS STEM - R.K.LEKSHMI; S. MINI (International Journal of Pharma and Bio Sciences, 2013)
The present study evaluated the free radical scavenging capacity and antioxidant potential of different solvent fractions (Petroleum ether, Ethyl acetate, Butanol and Water) of methanolic extract of Cissus quadrangularis stem. Ethyl acetate fraction of Cissus quadrangularis stem possessed a high amount of total phenolic and flavonoid contents as compared to other solvent fractions. Also Ethyl acetate fraction exhibited maximum scavenging activity against DPPH (IC50 62.53±5.71μg/ml), superoxide (IC50 50.7±4.86μg/ml), hydroxyl (IC50 24.38±2.34μg/ml) and nitric oxide radicals (IC50 33.83± 3.09μg/ml). These fractions were also screened for their antidiabetic activity via antiglycation assay. Results showed that the ethyl acetate fraction exhibited higher antiglycation activity. Significant antiglycation activity also confirms the therapeutic potential of these fractions against diabetes.